Public Danger and Wrongfulness as Important Signs of Administrative Offences Related to Unauthorized Occupation of a Land Plot - Кельман, Михайло Степанович; Кельман, М. С.; Кельман, Михаил Степанович; Kelman, Mykhailo S.; Токарська, Антоніна Семенівна; Токарська, А. С.; Токарская, Антонина Семеновна; Tokarska, Antonina S.; Бисага, Юрій Михайлович; Бисага, Ю. М.; Бисага, Юрий Михайлович; Bysaha, Yurii M.; et al. (Allied Business Academies, 2020)
Description: The purpose of the article is to study public danger and wrongfulness as the main signs of administrative offense related to unauthorized occupation of a land plot. Methodology: The methodological basis of the study is dialectical-materialistic and formal-logical methods of scientific knowledge and general scientific and special methods based on them. This allowed researching the problem in the unity of its social content and legal form. The results of the study: On the basis of the analysis of scientific views of scientists and the norms of the current legislation of Ukraine, the characteristic of such signs of administrative offense related to unauthorized occupation of the land plot, as public danger and wrongfulness have been examined. Practical implications. Having taken note of the analysis of legal acts adopted during the studied period we can conclude that the assertion of the Soviet authorities was accompanied by the increased criminal liability for violations in the area of land use. Value/originality: It has been stated that public danger of the offense directly affects the severity of punishment. In turn, such a sign as wrongfulness indicates the inability to apply law analogy, that is, precludes the possibility of bringing a person to administrative liability, if the act committed is not directly enshrined in administrative law.

Опис: Метою статті є дослідження суспільної небезпеки та протиправності як основних ознак адміністративного правопорушення, пов’язаного із самовільним зайняттям земельної ділянки. Методологія: Методологічною основою дослідження є діалектико-матеріалістичні та формально-логічні методи наукового пізнання та загальнонаукові та спеціальні методи на їх основі. Це дозволило досліджувати проблему в єдності її соціального змісту та правової форми. Результати дослідження: На основі аналізу наукових поглядів науковців та норм чинного законодавства України визначено характеристику таких ознак адміністративного правопорушення, пов’язаного із самовільним зайняттям земельної ділянки, як суспільна небезпека та протиправність. Практичні наслідки. Беручи до уваги аналіз нормативно-правових актів, прийнятих за досліджуваний період, можна зробити висновок, що твердження радянської влади супроводжувалося посиленням кримінальної відповідальності за порушення у сфері землекористування. Цінність/оригінальність: Вказано, що суспільна небезпека правопорушення безпосередньо впливає на суворість покарання. У свою чергу, така ознака, як протиправність, свідчить про неможливість застосування аналогії права, тобто виключає можливість притягнення особи до адміністративної відповідальності, якщо вчинене діяння прямо не закріплено адміністративним законодавством.
Kelman M. Public Danger and Wrongfulness as Important Signs of Administrative Offences Related to Unauthorized Occupation of a Land Plot / M. Kelman, A. Tokarska, Yu. Bysaha, K. Zhebrovska, O. Oliinyk // Journal of Legal, Ethical and Regulatory Issues. – Vol. 23. - Issue 2. - Allied Business Academies, 2020. – P. 1-6.
Keywords: administrative misconduct; responsibility; social danger; illegality; wrongfulness; land plot; unauthorized occupation; адміністративний проступок; відповідальність; соціальна небезпека; незаконність; протиправність; земельна ділянка; самовільне зайняття; Research Subject Categories::LAW/JURISPRUDENCE